AB0308 NO SIGNS OF CONGESTIVE HEART DISEASE PROGRESSION IN PATIENTS WITH RHEUMATOID ARTHRITIS ON IL-6 RECEPTOR ANTAGONIST AFTER 12 MONTHS TREATMENT. (13th June 2020) - Martynova, A.; Popkova, T.; Gerasimova, H.
Abstract : Background: N-terminal pro-brain natriuretic peptide (NT-proBNP) is a known marker of heart dysfunction, mainly described in patients with high activity of rheumatoid arthritis (RA). Further knowledge of the influence of the IL-6 receptor antagonist, tocilizumab (TCZ), on NT-proBNP levels and systolic heart function is yet to be obtained. Objectives: Access the effect of 12 months TCZ therapy on NT-proBNP levels, transthoracal ehocardiography results and analyze the association between congestive heart disease progression and RA activity. Methods: 37 RA patients (pts) (31F/6M); median age 56, 5 [48; 63, 5] years; disease duration 48 [6; 348] months; DAS28 score 6, 15 [5, 44; 6, 45]; rheumatoid factor (RF)+100%; anti–citrullinated protein antibody (ACPA) + 79, 6% were treated in an open-label study with TCZ (8 mg/kg every 4 weeks). Identification of NT-pro-BNT in blood serum, transthoracal ultrasound evaluation of left ventriculum ejection fraction (LVEF), E/A ratio performed at baseline and 12 months. Results: 11 (29, 7%) pts had congestive heart disease (CHD) (II functional class of NYHA), 7 (18, 9%) pts having signs of mild left ventricular dysfunction (LVD) as dyspnea, shortness of breath, cardiotropic treatment remained the same in the course of the study. After 12 month TCZ treatment as RA activity lowered (DAS28 2.32 [1, 75; 3, 15], р<0, 05), NT-proBNP levels decreased (100, 95 [57.9; 117.6] pg/ml to 90, 46 [33.62; 106.6] pg/ml), along with elevation of LVEF (60, 75 [60; 70]% to 67, 68 [62.5; 73.5], p = 0, 001). Increase of E/A (0, 97 [0.8; 1.17] to 1, 04 [0.7; 1.42] correlated with decrease of NT-proBNP level (r = -0, 63, p=0, 036). Raise of LVEF over 12 months correlated with decrease of RA activity according to SDAI scale (r= -0, 670, p<0, 05). No significant relationship between NT-proBNP levels, LVEF, E/A and other scales measuring RA activity was found. Clinically all patients had improvement in evaluation of their health and no signs of CHD or RVD progression were found. Conclusion: Use of TCZ in patients with active RA showed none to positive influence on heart condition, specifically, lowering NT-proBNP levels, improving LVEF and reducing clinical signs of LVD. References: [1]Pan Y, Li D, Ma J, Shan L, Wei M. NT-proBNP test with improved accuracy for the diagnosis of chronic heart failure. Medicine (Baltimore). 2017 Dec;96(51):e9181. [2]D Novikova, I Kirillova, E Markelova et al. The first report of significantly improvement of NT-proBNP level in rheumatoid arthritis patients treated with tofacitinib during 12-month follow-up, European Heart Journal, Volume 40, Issue Supplement_1, October 2019, ehz745.0836. [3]Pappas DA, Nyberg F, Kremer JM et al. Clin Rheumatol. 2018 Sep;37(9):2331-2340. Disclosure of Interests: None declared